2013
DOI: 10.1007/s11434-013-6026-5
|View full text |Cite
|
Sign up to set email alerts
|

Further geological and palaeoanthropological investigations at the Maludong hominin site, Yunnan Province, Southwest China

Abstract: Three-dimensional mapping and section work undertaken by us in 2008 have identified 11 stratigraphic units at Maludong site. AMS radiocarbon dating of charcoal established an accurate and internally consistent age profile for the sequence of 17.8±0.2 ka to 13.2±0.1 ka. Archaeomagnetic analysis showed changes in externally derived pedogenically enhanced material consistent with a warming in climate between the cold period of Henrich Event 1 and the Bølling-Allerød interstadial. Human remains recovered during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…In the case of the unusual cranium from Longlin Cave [ 24 ], it was recently concluded that its mosaic morphology probably results from hybridisation between AMH and an unknown archaic species, perhaps even occurring during the early Holocene [ 26 ]. A similar explanation might also apply to the morphology of the Maludong cranial fossils [ 24 , 25 ], a hypothesis currently under investigation by us. Here we report a partial proximal femur from Maludong (Yunnan), Southwest China, found in association with these unusual cranial remains, which shows morphological and phylogenetic affinities to archaic hominins.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…In the case of the unusual cranium from Longlin Cave [ 24 ], it was recently concluded that its mosaic morphology probably results from hybridisation between AMH and an unknown archaic species, perhaps even occurring during the early Holocene [ 26 ]. A similar explanation might also apply to the morphology of the Maludong cranial fossils [ 24 , 25 ], a hypothesis currently under investigation by us. Here we report a partial proximal femur from Maludong (Yunnan), Southwest China, found in association with these unusual cranial remains, which shows morphological and phylogenetic affinities to archaic hominins.…”
Section: Introductionmentioning
confidence: 63%
“…Several of the current authors have previously reported the occurrence of hominin cranial remains from two sites in Southwest China (Maludong and Longlin or Laomaocao Cave) that combine archaic hominin and AMH traits [ 24 , 25 ]. In the case of the unusual cranium from Longlin Cave [ 24 ], it was recently concluded that its mosaic morphology probably results from hybridisation between AMH and an unknown archaic species, perhaps even occurring during the early Holocene [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have questioned our findings and argued that these fossils instead show affinities to either the Late Pleistocene Upper Cave remains from Zhoukoudian18 or Late Pleistocene/early Holocene crania from mainland Southeast Asia19. A recently described mandible from Tam Pa Ling (TPL2) in nearby Laos has also been described as exhibiting archaic hominin features20, although, they are far less numerous than those seen in the Maludong or Longlin remains1516. The similarly dated TPL1 cranium is evidently modern in its morphology19.…”
mentioning
confidence: 69%
“…1), we documented an extensive number of traits that would be unexpected for a modern human, some of them putative plesiomorphies for Late Pleistocene Homo : a finding unseen for any cranium from East Asia during this period and unusual even among Late Pleistocene remains globally1516, including Australians17. We suggested that two most likely interpretations of the morphology of the Maludong and Longlin Cave fossils were1516: 1) they represent the remnants of a precociously early and highly plesiomorphic modern human population that migrated to the region and failed to contribute genetically, or did so in a limited way, to recent people, or 2) they sample a late surviving archaic hominin population.…”
mentioning
confidence: 96%
See 1 more Smart Citation